The Cuban Treefrog (Osteopilus septentrionalis) in Florida - Steve A Johnson (EDIS, 2023)
Florida is the global epicenter for introduced nonnative reptiles and amphibians. These include well-known species such as Burmese pythons and green iguanas as well as dozens of other species of snakes, lizards, and frogs. There are four species of nonnative frogs currently established in Florida. The purpose of this publication, a UF/IFAS numbered Organism ID., is to summarize the status, biology, and impacts of one of those frogs, the Cuban treefrog. The publication also presents strategies to manage Cuban treefrogs to help alleviate human conflicts and benefit native species. The main target audience is homeowners who suspect they have Cuban treefrogs on their property and/or need technical assistance dealing with these often-problematic frogs. Environmental educators, natural resource managers, and professional scientists will also find the information herein of interest.